Hobby Store / Amirul Shah Abdullah … [et al.] - Abdullah, Amirul Shah; Adnan, Mohammad Hakim; Mohd Ribuan, Mohd Khalid; Mohd Daud, Ahmad Rizal (2001)
Our business name is Hobby Store. The type of business that we will be doing is selling radio control models such airplanes, helicopters, cars and watercrafts and we also offer services related to the business. This type of business has been in the market of Malaysia for a long time ago. We have make a study about the business of radio control at a company named Hobby World Sdn Bhd. This company was establish since 1981. This company was known to be the pioneer company of the official distributor of radio control models in Malaysia. The models are imported from other countries such as Japan, United States of America, Korea and others .There are no manufacturer of this radio control models in Malaysia. All are imported things. We will run our business at No 40, Jalan Tengku Ampuan Zabedah B , 9/B Seksyen 9,41000 Shah Alam, Selangor.We planned that the business is commence on thelst January 2002. We decided to choose this radio control business because we feel that there is large opportunity that this business will be successful if commenced in Shah Alam. No of company that are selling this product is very limited and only focused on the Klang Valley only. In addition, this business is not done yet in Shah Alam. In the future, we think that this business can be very successful and can compete with other business as well. We also hope that our country can manufacture the radio control models and no longer have to import it.